Synthesis, Characterization and Antimicrobial Evaluation of (E)-N’-[(1-(2-methoxy-6-pentadecylbenzyl)-1H-1,2,3-triazol-4-yl]methylene)benzohydrazide Derivatives - Rambabu, N.; Dubey, P.K.; Ram, B.; Balram, B. (Asian Journal of Chemistry, 2015)
Anacardic acid (pentadecyl salicylic acid) is a phenolic constituent present in cashew nut shell liquid (Anacardium occidentale L.) and exhibits antimicrobial properties. The present paper describes the synthesis, characterization and antimicrobial evaluation of hydrazone derivatives of anacardic acid (9a-l) linked with 1,2,3-triazole ring. All the newly synthesized compounds were determined by 1H NMR, mass and IR spectroscopy. Compounds 9d, 9e, 9h, 9i and 9j exhibited strong antifungal activity against the tested fungal strains viz., A. niger and C. albicans.